Optimizing Carbon Stocks and Sedimentation in Indonesian Mangroves under Different Management Regimes - Murdiyarso, D.; Arifanti, V.B.; Sidik, F.; Sillanpää, M.; Sasmito, S.D. (Wiley, 2021)
Mangrove ecosystems are widely distributed across Indonesia's shores and benefit coastal societies through their valuable ecosystem goods and services. These coastal forests sequester and store large amounts of atmospheric carbon as forms of biomass, necromass, and organic soil or sediment. This substantial carbon storage capacity is now being recognized and promoted in nature-based climate change mitigation and adaptation strategies. Over the past decade, we have conducted extensive assessments of mangrove carbon storage across the archipelago to understand mangrove's natural variation and response to various management regimes. Approximately 3 million ha of mangroves in Indonesia store more than 3 billion tons of carbon, however these ecosystems also face tremendous conversion pressure. Indonesian mangroves must therefore be managed innovatively to minimize further degradation and optimize ecosystem functions. Here, we summarize carbon stocks and sequestration across four different mangrove management regimes, namely protected, degraded, converted, and restored mangroves. Mangroves in Indonesia are able to recover from degradation, and sequester substantial amounts of carbon, between 1 and 10 tons (metric) C/ha/yr. Sediment accretion rates (SAR) between 4 and 6 mm/yr were also observed, potentially protecting low-lying coastal zones from susceptibility to contemporary sea-level rise and flooding. Existing information on the total economic valuation (TEV) of mangroves, which at the landscape scale can be up to USD 29 million, suggests that management regimes should also focus on the ecosystem goods and services provided by mangroves. Here we discuss a variety of management regimes that respond to the unique characteristics of the local mangrove setting, optimizing carbon sequestration and storage functions, and promoting conservation and restoration, so as to achieve sustainable livelihoods.